Discussion on development trends and utilization efficiency enhancement of LNG terminals in China - Yi WU; Ran LI; Dandi ZHANG (You-qi chuyun)
Objective China has significantly accelerated the construction of liquefied natural gas (LNG) terminals in recent years. The terminal infrastructure for unloading imported LNG resources through ocean transport has established a sea passage for China's natural gas imports, which hold a critical position in the nation's energy mix. Therefore, analyzing development trends and exploring strategies to enhance the utilization efficiency of LNG terminals are immensely significant to ensure national security in energy supply and promote the diversification of the natural gas market. Methods This study delved into the developmental trajectory of LNG terminals in China, starting from the inauguration of the Dapeng LNG Terminal in 2006 in Guangdong as China's first of its kind, and particularly focusing on the period following the establishment of the China Oil and Gas Pipeline Network Corporation in December 2019, and offered insights into future trends. An analysis was undertaken to scrutinize the supply of LNG resources through long-term import agreements and the surplus capacity of LNG terminals within China. Moreover, in-depth discussions revolved around tactics and practices to enhance the utilization efficiency of these LNG terminals, such as the issuance of guidance at the national level to bolster the fairness and openness of LNG terminals, compliance with fairness and openness requirements for LNG terminals across operators of pipeline network facilities, and the introduction of innovative measures concerning the openness of LNG terminals by resource supply enterprises. Results The ongoing expansion of natural gas consumption and the increasing influx of imported LNG in China's market have created a conducive environment for heightened investment, development, and construction within the country's LNG industry. Technological advancements and continual upgrades in China's energy sector have opened up possibilities for significantly enhancing the energy utilization efficiency of these LNG terminals and curbing operational expenses, thereby bolstering a more dependable and steady LNG supply chain. Nevertheless, looking through a long-term lens, China confronts the challenge of declining utilization efficiency in its LNG terminals. Conclusion This paper concludes with recommendations for the development of LNG terminals in China, which include: (1) meeting supply guarantee obligations, and systematically opening terminals; (2) accelerating infrastructure development, expediting mutual guarantee, mutual supply, and interconnection construction, and ensuring stable consumption under long-term agreements; (3) innovating international trade approaches, optimizing preferential tariff policies, and consistently enhancing terminal utilization efficiency.